High-fat diet increases respiratory frequency and abdominal expiratory motor activity during hypercapnia - Speretta, Guilherme F. [UNESP]; Lemes, Eduardo [UNESP]; Vendramini, Regina C. [UNESP]; Menani, José V. [UNESP]; Zoccal, Daniel B. [UNESP]; Colombari, Eduardo [UNESP]; Colombari, Débora S.A. [UNESP]; Bassi, Mirian [UNESP] (Elsevier, 2018)
Breathing disorders are commonly observed in association with obesity. Here we tested whether high-fat diet (HFD) impairs the chemoreflex ventilatory response. Male Holtzman rats (300–320 g) were fed with standard chow diet (SD) or HFD for 12 weeks. Then, tidal volume (V T ), respiratory frequency (f R ) and pulmonary ventilation (V E ) were determined in conscious rats during basal condition, hypercapnia (7% or 10% CO 2 ) or hypoxia (7% O 2 ). The mean arterial pressure (MAP), heart rate (HR) and baroreflex sensitivity were also evaluated in conscious rats. A group of anesthetized rats was used for the measurements of the activity of inspiratory (diaphragm) and expiratory (abdominal) muscles under the same gas conditions. Baseline f R , V T and V E were similar between SD and HFD rats. During hypercapnia, the increase of f R was exacerbated in conscious HFD rats (60 ± 3, vs. SD: 47 ± 3 Δ breaths.min −1 , P < 0.05). In anesthetized rats, hypercapnia strongly increased abdominal muscle activity in HFD group (238 ± 27, vs. basal condition: 100 ± 0.3%; P < 0.05), without significant change in SD group (129 ± 2.1, vs. basal condition: 100 ± 0.8%; P = 0.34). The ventilatory responses to hypoxia were similar between groups. In conscious HFD rats, MAP and HR were elevated and the baroreflex function was impaired (P < 0.05). These data demonstrated that 12 weeks of HFD exaggerate the ventilatory response activated by hypercapnia. The mechanisms involved in these responses need more investigation in future studies.
Keywords: Baroreflex; Blood pressure; Chemoreflex; Diaphragm motor activity; Hypoxia; Sympathetic modulation